Assessment of Railway Steel Bridge Structures. (2016) - Bujňák, Ján; Gocál, Jozef; Hlinka, Richard
Abstract: The assessment of an existing structure producing the evidence that it will function safely over a specified residual service life should be also a continuous activity to ensure the security of the public. Usually bridges were designed by safe life method and a limited serviceability was considered. Such structure requires to be replaced once this designed durability would be achieved. This is however often not possible since most of the infrastructure cannot be economically taken out of service. Alternatively, the damage tolerant method should provide an acceptable reliability that a structure will perform reasonably for its service. But a prescribed inspection and maintenance regime for detecting and correcting fatigue damage should be identified. The present practice is illustrated in the paper by case studies on existing railway bridges under exploitation. Procedures for service-load- level analyses are given to estimate the residual service life.